EDUKASI PEMASARAN BATA MERAH RAMAH LINGKUNGAN PADA KELOMPOK PENGRAJIN SENDEN JAYA, KLATEN - Alfia Magfirona; Rumaisa Hisan; Muzakar Isa; Muhammad Ujianto; Nabil Belantara Kusuma; Nila Kusuma Ayu Lestari; Akmal Wicaksono; Mochammad Geraldy (LPPM Institut Pendidikan Nusantara Global, 2025)
The problem of wood waste, particularly wood dust, is a pressing environmental issue for the furniture industry in Senden Village, Ngawen District, Klaten Regency. Waste that is usually burned or piled up causes pollution and impacts public health. The innovation of processing waste into environmentally friendly red bricks is a solution that has a selling value, is lighter, has good thermal insulation, and supports the eco-friendly concept. However, the artisan group still faces obstacles in the traditional marketing aspect. The objective of this community service activity is to analyze and implement marketing strategies, specifically through a digital approach, for the Senden Jaya Furniture Artisan Group. The activity methods include outreach, workshops, mentoring, and evaluation with the involvement of partner members as the main active participants. The results show an increase in partner skills in utilizing digital platforms such as Tokopedia as an online sales channel and TikTok and Instagram as creative promotional tools. Based on the post-test results, participants' understanding of digital marketing has significantly increased, and the product's image as an environmentally friendly brick has improved. These findings demonstrate that digital marketing strategies are effective in increasing partner economic value while supporting sustainable waste management.